College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.8 - One-to-One Functions and their Inverses - 2.8 Exercises: 58

Answer

$f^{-1}(x) = \frac{x + 2}{4 - 3x}$

Work Step by Step

$f(x) = \frac{4x - 2}{3x + 1}$ $y = \frac{4x - 2}{3x + 1}$ y(3x + 1) = 4x - 2 3xy + y = 4x - 2 y + 2 = 4x - 3xy y + 2 = x(4 - 3y) $x = \frac{y + 2}{4 - 3y}$ $f^{-1}(x) = \frac{x + 2}{4 - 3x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.